Arduino-Based Automatic Rice Vending Device - Hugeng, Hugeng; Yapito, Mikael Christian; Suraidi (Jetri : Jurnal Ilmiah Teknik Elektro, 2024)
Indonesian rice shops carry out the weighing process manually and in-a-hurry, so that it often makes the weighing incorrect. The built vending device can work automatically in weighing rice. It can weigh 2 types of rice and sold per kilogram. It consists of a processor module, input module, output valve drive module, indicator module and limit switch module. The processing module uses Arduino Nano; input module uses a push button that is used to select the type of rice. The output valve drive module uses a servo motor that functions to move the output channel valve so that the rice can come out of the container. The indicator module uses a buzzer that functions to provide information if there is little rice left in the storage tank. The limit switch module functions to detect rice cans on the rice output valve and functions as a reset button. If there is little rice left in the storage can, it is necessary to replenish the rice stock. The outgoing rice storage can has a capacity of one kg of rice. The built automatic system can increase efficiency in selling rice and productivity of the seller. The designed device does not use weight sensors or scales, however it has a difference in rice weight that is no more than 15 grams.